Poisonous skies acid rain and the globalization of pollution - Rothschild, Rachel Emma (The University of Chicago Press, 2019)
Poisonous Skies explores how scientists and policymakers came to grasp the danger fossil fuels posed to the global environment by looking at the first air pollution problem identified as having damaging effects on areas far from the source of emissions: acid rain. This is the first history to investigate acid rain in an international context, spanning from its identification in the 1960s to the present day. The story Rachel Emma Rothschild unfurls reveals how a legacy of military sponsorship of physics, chemistry, and other fields during wartime influenced the direction of research on the environment; the importance of environmental diplomacy to the d tente process of the Cold War; the role of the British and American coal industries in environmental science; and finally, how acid rain shaped ideas about environmental risk and the precautionary principle. Grounded in archival research in eight different countries and five languages as well as interviews with leading scientists from both government and industry, Poisonous Skies should interest anyone seeking to learn from our past in order to better understand and approach the environmental crises of our present day